Peran Ayah dalam Pengasuhan Anak di Keluarga Urban - Irawan, Wanwan (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2024)
This study explores the role of fathers in childcare in Jambi urban families, focusing on the challenges faced, the strategies implemented, and the impact of fathers' involvement on child development. Through in-depth interviews with several fathers and direct observation in the household, the study identified that open communication, positive rewards, skill teaching, and examples of good behavior are effective strategies that fathers use in parenting. However, fathers also face various obstacles such as work pressure and rigid social expectations regarding gender roles. This study shows that social support and policies that facilitate work-life balance are essential to increase fathers' involvement in parenting. The results of this study have implications for the development of policies and programs that support the role of fathers, with the aim of creating a more inclusive and supportive parenting environment for children and families in Jambi.